1993
DOI: 10.1021/jm00072a004
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and relative potencies of new constrained CRF antagonists

Abstract: Two series of CRF antagonists with N alpha- and C alpha-methylated alanine and leucines were evaluated for their biological activities in vitro and in vivo in several systems. The poly-N-methylated analogue of alpha-helical-CRF9-41, [N alpha MeLeu10,15,27,37,N alpha MeAla22,32,41]-alpha-Hel-CRF9-41, was found to be considerably less potent than the parent non-N-methylated analogue. This result was expected on the basis that alpha-helicity was thought to be required for biological activity and the prediction th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
93
0
3

Year Published

2000
2000
2017
2017

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 87 publications
(97 citation statements)
references
References 15 publications
1
93
0
3
Order By: Relevance
“…Our findings in the UCN 4-15 template correlate perfectly with an early single point D-substitution study on the full length CRH endogenous hormone . It is noteworthy that the D-Phe substitution was systematically used for the synthesis and SAR studies of CRHR 1 peptide agonists and antagonists (Cervini et al 1999;Gulyas et al 1995;Hernandez et al 1993;Koerber et al 1998;Miranda et al 1994;Miranda et al 1997;Rivier et al 1998a;Rivier et al 1998b …”
Section: -15mentioning
confidence: 99%
“…Our findings in the UCN 4-15 template correlate perfectly with an early single point D-substitution study on the full length CRH endogenous hormone . It is noteworthy that the D-Phe substitution was systematically used for the synthesis and SAR studies of CRHR 1 peptide agonists and antagonists (Cervini et al 1999;Gulyas et al 1995;Hernandez et al 1993;Koerber et al 1998;Miranda et al 1994;Miranda et al 1997;Rivier et al 1998a;Rivier et al 1998b …”
Section: -15mentioning
confidence: 99%
“…A variety of CRH antagonists have been synthesized, beginning with the early modifications of CRH itself that resulted in a-helical CRH (Rivier et al, 1984) and D-Phe CRH (Hernandez et al, 1993;Menzaghi et al, 1994), and extending to the more recent analogs, astressin (Gulyas et al, 1995) and the longer-lasting astressin B . Nonpeptidic compounds, the so-called 'small molecule' CRH-R1 selective antagonists, such as CP-154,526 (Schulz et al, 1996), its methyl analog, antalarmin (Webster et al, 1996; see also review by McCarthy et al, 1999), and SSR125543A (Griebel et al, 2002) have been investigated preclinically using animal models of depression and anxiety.…”
Section: Introductionmentioning
confidence: 99%
“…The high-affinity carrier peptides 1-3 share common and specific structural features: all three possess an intramolecular lactam bridge. This conformational constrain is well characterized and has been shown to stabilize the peptide's helical conformation thus enhancing its affinity for the CRHR 1 -ECD1 (Gulyas et al 1995;Hernandez et al 1993;Koerber et al 1998;Miranda et al 1994;Rivier et al 1998b). Similarly, recent structure-activity-relationship studies have identified the cyclohexyl-alanine (X) substitution to be greatly potency enhancing (Yamada et al 2004).…”
Section: Synthesis and Characterization Of Crhr 1 -Ecd1 High Affinitymentioning
confidence: 99%
“…Our findings in the UCN 4-15 template correlate perfectly with an early single point D-substitution study on the full length CRH endogenous hormone . It is noteworthy that the D-Phe substitution was systematically used for the synthesis and SAR studies of CRHR 1 peptide agonists and antagonists (Cervini et al 1999;Gulyas et al 1995;Hernandez et al 1993;Koerber et al 1998;Miranda et al 1994;Miranda et al 1997;Rivier et al 1998a;Rivier et al 1998b). To further probe the role of the Phe 11 residue for the potency of ligands, we decided to synthesize a library of UCN 4-15 conjugates bearing Phe 11 substitutions.…”
Section: Structure-activity-relationship At [Phe 11 ]Ucn 4-15mentioning
confidence: 99%